Growing yourself as a leader : technical leadership capabilities - Sutton, Brian; Chatham, Robina (BCS Learning & Development Limited, 2018)
With real life examples, tips and mini exercises, this book describes six management techniques that will help you develop your leadership capabilities and grow as a leader, including unlocking your creative potential, learning by developing oth.